In the House of Representatives, December 27. 1755. : Whereas a considerable number of the inhabitants of Nova-Scotia arrived here the 26th instant, being removed by the governour and Council of that province for the security thereof ... Ordered, that Mr. James Russell, Mr. Cooper, and Mr. Hall, which such as the honourable board shall join, be a committee to provide for the support of such inhabitants of Nova-Scotia . ([Printed by S. Kneeland], 1755)
December 29, 1755 House order to establish a process in towns for the reception of refugees from Nova Scotia, particularly until the governor gives his orders regarding same.